Measuring consumers’ preferences for craft beer attributes through Best-Worst Scaling - Marco Lerro (Agricultural and Food Economics, 2020)
Abstract The current paper investigates consumers’ consumption behavior and preferences for craft beer. More specifically, it uncovers consumers’ consumption habits and perception about craft beer, as well as their preferences for 13 beer attributes drawn from the literature. The analysis was carried out in Italy by administering a structured questionnaire to 323 consumers. Best-Worst Scaling was used to detect consumers’ preferences towards the 13 craft beer attributes. The latter were then ranked on the basis of their best-worst scores to identify the level of importance Italian consumers assign to the different attributes. The study findings reveal that Italian craft beer consumers are young, well-educated, and employed. They drink craft beer more than once per month, mainly in pub and with friends and colleagues. Craft beer is perceived with higher quality and different flavors, while compared with a commercial beer, it results tastier, more genuine, and natural. As for the beer attributes, Italians prefer taste, fermentation process, and color, while store promotion, brand, and price rank as the least important. The study findings offer several implications for brewers and marketers involved in the beer sector. Based on the preferences detected, breweries should adapt their product offer to meet craft beer consumers’ expectations.